Acute Infection of Viral Pathogens and Their Innate Immune Escape - Rai, Kul Raj; Shrestha, Prasha; Yang, Bincai; Chen, Yuhai; Liu, Shasha; Maarouf, Mohamed; Chen, Ji-Long (Frontiers in Microbiology, 2021)
Viral infections can cause rampant disease in human beings, ranging from mild to acute, that can often be fatal unless resolved. An acute viral infection is characterized by sudden or rapid onset of disease, which can be resolved quickly by robust innate immune responses exerted by the host or, instead, may kill the host. Immediately after viral infection, elements of innate immunity, such as physical barriers, various phagocytic cells, group of cytokines, interferons (IFNs), and IFN-stimulated genes, provide the first line of defense for viral clearance. Innate immunity not only plays a critical role in rapid viral clearance but can also lead to disease progression through immune-mediated host tissue injury. Although elements of antiviral innate immunity are armed to counter the viral invasion, viruses have evolved various strategies to escape host immune surveillance to establish successful infections. Understanding complex mechanisms underlying the interaction between viruses and host’s innate immune system would help develop rational treatment strategies for acute viral infectious diseases. In this review, we discuss the pathogenesis of acute infections caused by viral pathogens and highlight broad immune escape strategies exhibited by viruses.